Existential Well-Being in Relation to Mental Health: A Quantitative Study - Tongue,Christine; Lidforsen,Diana (2026)
The aim of this study was to examine the relationship between existential health and general mental health, specifically to investigate how individuals with higher and lower levels of mental well-being differ in their Purpose in Life and to measure which dimensions of Purpose in Life contribute the most strongly to mental well-being. Grounded in Frankl’s existential theories, this study used the Purpose in Life, PIL-20 scale, combined with GHQ-12 to measure mental health. The data were collected via a digital survey through convenience sampling in the general Swedish population (N=101). The results found that Purpose in Life is strongly associated with general mental health: participants reporting better mental health also scored higher on Purpose in Life, and vice versa. A correlational analysis showed that GHQ index was strongly associated with the PIL index, while correlations with individual PIL factors ranged from strong to moderate, with Meaning in Existence showing the strongest relationship. It was found that the dimensions Meaning in Existence and Freedom to Create Meaning contributed significantly to predicting GHQ scores, while Will to Meaning did not. These findings have value for mental health professionals and contribute to the often overlooked topic of existential health.
Keywords: Existential health; purpose in life; general mental health; Existentiell hälsa; meningsfullhet; generell psykisk hälsa